DEVELOPMENT OF REGULATIONS ON VOTING RIGHTS PEOPLE WITH MENTAL DISORDERS POST-CONSTITUTIONAL COURT RULING APPLIED - Oktari, Tanti (Sekolah Tinggi Ilmu Hukum Awang Long, 2023)
This research only focuses on the regulation of the right to vote in general elections, whether at the national or regional level, for people with mental disorders. The general paradigm is very varied regarding the mental condition of people with mental disorders. There is a crucial ambiguity regarding the intellectual capacity of people with mental disorders. The effect of the debate concerns granting them the right to vote as a constitutional right. This research aims to explore further the legal politics of regulating the right to vote for people with mental disorders in Indonesia. The research method used is normative legal research with a statutory and comparative approach. The results of this research show that people with mental disorders are subjects who are excluded from being granted the right to vote. This is confirmed in Article 57 paragraph (3) letter a of Law Number 8 of 2015. The meaning of this provision has shifted after Constitutional Court Decision Number 135/PUU-XIII/2015. Restrictions are granted only in cases of mental disorders and/or permanent memory according to mental health professionals who have lost the ability to choose. The ratio decidendi which is the argument is that the condition of people with mental and/or memory disorders is not permanent enough to eliminate their intellectual capacity to choose. As a result, people with mental disorders can participate in voting in national or regional elections as long as they are not declared by mental health professionals to be incompetent to vote.